SYNERGY OF HUMANITARIAN AND MATHEMATICAL KNOWLEDGE AS A PEDAGOGICAL CONDITION FOR SOLVING INTERDISCIPLINARY PROBLEMS - Svetlana N. Dvoryatkina; Angelika A. Dyakina; Svetlana A. Rozanova (National Research Mordova State University, 2017)
Introduction: the article is concerned with the topical problem of the humanitarian and mathematical knowledge synergy in the context of solving important crosscutting issues. Since the authors have given a theoretical justification of mathematical integration of humanitarian and information knowledge and its implementation in the educational activities of universities. There is a description of the genesis and the main aspects of synergy. It is shown that the synergy of mathematical and humanitarian knowledge with using information technology is the complex educational environment dominant approach to many inter¬disciplinary problems. Materials and Methods: the synergetic approach is a conceptual framework for solving cross-cutting problems. The initial, exploratory and training options of the experimental research method are used to identify synergies problems of humanitarian and mathematical knowledge; mathematical modeling method is applied in solving professional problems for the development of a probabilistic model of analysis and comparison of styles of text works. Results: the complex of pedagogical conditions is defined, substantiated and tested, taking into account the dominant synergy of humanitarian and mathematical knowledge through the developed integrative course. The draft of the integrative course "Mathematical Methods in Linguistics" is presented; the optimum modular structure of the course is defined ("Formation of Modern Mathematics as a New Cultural Paradigm", "Basic Mathematical Concepts in Linguistics", "Mathematical Methods in Linguistics"); the essential elements of every mathematical module are practice-oriented tasks of philol ogical contents. Discussion and Conclusions: the synergy of mathematics and humanities is highly productive thing in scientific and research activities of students and in the learning process. The submitted materials can be included in lectures, practical exercises, integrative and interdisciplinary academic programmes.